Short-term heat treatment of Ti6Al4V ELI as implant material - Phuong Thao Mai; Bormann, Therese; Sonntag, Robert; Kretzer, Jan Philippe; Gibmeier, Jens (Materials, 2020)
Due to its mechanical properties and good biocompatibility, Ti6Al4V ELI (extra low interstitials) is widely used in medical technology, especially as material for implants. The specific microstructures that are approved for this purpose are listed in the standard ISO 20160:2006. Inductive short-term heat treatment is suitable for the adjustment of near-surface component properties such as residual stress conditions. A systematic evaluation of the Ti6Al4V microstructures resulting from short-term heat treatment is presently missing. In order to assess the parameter field that leads to suitable microstructures for load-bearing implants, dilatometer experiments have been conducted. For this purpose, dilatometer experiments with heating rates up to 1000 °C/s, holding times between 0.5 and 30 s and cooling rates of 100 and 1000 °C/s were systematically examined in the present study. Temperatures up to 950 °C and a holding time of 0.5 s led to microstructures, which are approved for medical applications according to the standard ISO 20160:2006. Below 950 °C, longer holding times can also be selected.